The problem of the centrality of oil and gas management in Iraq beyond 2005 The conflict between the Kurdistan Regional Government and Iraq’s federal model - واوۆسجاى یاریدەدەر شااڵو عبدامخامق وحىد; واوۆسجاى یاریدەدەر سٍرثیپ خامص حسیي (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Decentralizing political and economic authorities is one of the strongest problems inside new Iraqi government after Saddam Hussein’s regime. The main complicated problems for the Iraqi government is to decentralize is managing and controlling oil and gas relying on the Iraqi new constitution. Since, the Iraqi federal parliament could not issue the oil and gas law depending on Iraqi new constitution, so from 2007 till now the conflicts step by step has grown significantly between the Iraqi federal government in Baghdad and Kurdistan region government in Erbil. Now after 13 years in rebuilding the Iraqi new government, controlling and managing the oil& gas fields is one of the highest problem between federal and regional governments in Iraq, because the Iraqi federal government want to centralize these powers under its authority. For solving this problem, Iraqi parliament has to issue the new oil and gas law relying on the Iraqi new constitution. These laws have to give some effective powers for local and regional governments; that let these governments to manage and rule their natural resources, as long as does not contradict the policies and interests of the federal government in Baghdad. In contrast, these laws must give powers to accountable representation in parliament for monitoring the process of managing and controlling oil and gas between federal and regional governments inside Iraq.